After the black death a social history of early modern Europe - Huppert, George, 1934- (Interdisciplinary studies in history., 1998)
Leads the reader into the villages and cities of early modern European society. The book begins with an overview of family and community structure, social conflict, and religious beliefs. After describing the fundamental traits of both rural and urban society, it considers the elites, armed rebellion, poverty, criminality, sexual behavior, and marriage practices. For this second edition, the author has added a new chapter on the incessant warfare that was characteristic of this age and on the transformation of warfare by the new commercial capitalism. -- from back cover.